2017
DOI: 10.1063/1.4968904
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic ray feedback in galaxies and active galactic nuclei

Abstract: Recent cosmological simulations of galaxy formation have demonstrated that feedback by star formation, supernovae and active galactic nuclei appears to be critical in obtaining realistic disk galaxies, to slow down star formation to the small observed rates, to move gas and metals out of galaxies, and to balance radiative cooling of low-entropy gas at the centers of galaxy clusters. However the particular physical processes underlying these feedback processes still remain elusive. In particular, these simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 61 publications
1
21
0
Order By: Relevance
“…CRs are modeled as a relativistic fluid with a constant adiabatic index of 4/3 in the two fluid approximation (Pfrommer et al 2016). …”
Section: Methods and Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…CRs are modeled as a relativistic fluid with a constant adiabatic index of 4/3 in the two fluid approximation (Pfrommer et al 2016). …”
Section: Methods and Setupmentioning
confidence: 99%
“…Indeed, recent hydrodynamical simulations of the formation and evolution of disk galaxies have shown that CR pressure can drive strong bipolar outflows in disk galaxies provided they are allowed to stream (Uhlig et al 2012;Ruszkowski et al 2016) or diffuse (Booth et al 2013; relative to the rest frame of the gas. However, they also showed that injecting CRs at supernova remnants and only accounting for their advective transport is not sufficient for launching winds (Jubelgas et al 2008;Pfrommer et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The ideal MHD prescription (Pakmor & Springel 2013) governs the evolution of the magnetic field. Starting from an initial seed magnetic field 𝐵 0 permeating the gas cloud before collapse, the magnetic field is exponentially amplified by a small-scale dynamo, before it grows further via an inverse cascade until saturation (Pfrommer et al 2021). We chose two different values for the initial magnetic field of 𝐵 0 = 10 −10 and 10 −12 G, which represent the pre-amplified magnetic field in a proto-galactic environment.…”
Section: Simulationsmentioning
confidence: 99%
“…For the FRC, we chose to calculate the radio luminosity for a face-on configuration of our galaxies. The corresponding edge-on luminosities are typically a factor of about two smaller, which introduces a natural scatter in the FRC (Pfrommer et al 2021). We correlate the face-on radio synchrotron luminosities against the SFR ( 𝑀 ★ ) of our simulated galaxies with an initial magnetic field of 𝐵 0 = 10 −10 G and 𝜁 SN = 0.05 in Fig.…”
Section: Modelling the Fir-radio Correlationmentioning
confidence: 99%
See 1 more Smart Citation